98.6k views
5 votes
If (x^2 – 4) = (x + 2) = x - 2, which polynomial should fill in the blank below?​

If (x^2 – 4) = (x + 2) = x - 2, which polynomial should fill in the blank below?​-example-1
User Kohlbrr
by
4.7k points

2 Answers

3 votes

Answer: B

Explanation:

User Dominic Hopton
by
5.3k points
4 votes

Hey there! :)

Answer:

2nd choice. (x - 2)

Explanation:

Given in the question:

(x²-4) ÷ (x + 2) = x-2

This is an example of difference of squares.

We can rearrange the equation by multiplying both sides by (x+2) to become:

(x² - 4) = x - 2 (x + 2)

Therefore, the binomial that must be multiplied by (x+2) is the second choice, x-2.

User Ruanhao
by
5.7k points